Peningkatan Profesionalisme Guru MGMP Biologi-SMA Kota Jayapura Melalui Pelatihan Aplikasi Taksonomi Numerik - Lisye I. Zebua; Supeni Sufaati; Suharno Suharno; Triwiyono Triwiyono (Jurusan Biologi FMIPA Universitas Cenderawasih, 2022)
Biology practicum activities in high school generally follow the cookbook method. The method contains a practicum manual that contains complete information on the sequence of practicum procedures that must be carried out by students. In addition, this method may cause student boredom and is also less challenging, less inspiring, and motivational to develop investigative skills. Therefore, a Biology teacher is required to innovate in developing inspiring teaching methods. To support these Biology teachers, they need to be equipped with knowledge and skills through courses or training with the material in the curriculum so that they can master the concepts of knowledge that are more up to date. This training activity aims to guide high school Biology MGMP teachers in designing and making learning innovations in Biodiversity material and to train them in applying numerical taxonomy concepts to Biodiversity material in the classroom. The method of activity used is direct observation and practice in the field by utilizing samples of fungi, plants, or animals in the surrounding environment. The teachers made and observed several herbarium specimens to obtain the morphological characters of these specimens. Furthermore, they have applied the concept of numerical taxonomy manually or by using the NTSYS-Program software. The final result of this activity has been composed of two modules and one numerical taxonomy practicum guide that can be used by Biology teachers and students.Keyword: Biology; numerical; taxonomy; training; teachers.Â